Simulation of ZVS Converter and Analysis of Its Switching Loss Based on PSPICE - Wang Xiaoyuan; Yang Zhe (International Journal of Power Electronics and Drive Systems (IJPEDS), 2012)
The working principle of Zero Voltage Switch (ZVS) inverter is presented in this paper. Simulations of the model are carried out with PSPICE. The loss of the inverter is analyzed with taking the actual situation into consideration. It is worthiness to practical engineering application.DOI: http://dx.doi.org/10.11591/ijpeds.v2i1.170